PENDATAAN DAN PENANGKARAN TANAMAN OBAT TRADISIONAL DARI HUTAN ISYO HILL RHEPANG MUAIF, DISTRIK NIMBOKRANG, KABUPATEN JAYAPURA - Agnes Eri Maryuni; Johnson Siallagan; Verena Agustini; Cheny Adetyaningsih (JURNAL PENGABDIAN PAPUA, 2020)
Rhepang Muaif is one of the villages in the Nimbokrang District, Jayapura. The aim of the activity was to eksplore and collect data of medicinal herbs from Isyo Hill’s Rhepang Muaif forest. Data showed that there were 28 plant species used traditionally by Isyo Hill’s people. Among them, 7 plants usually use to to cure cut, 21 other plants use to cure toothache, tumor, gallblade, uric acid, lung disease, headache, fever, malaria, rheumatic, to make the body slim and to improve stamina. This activity resulted herbarium, greenhouse with Rhepang’s medicinal herbs collections and a book that can be used to learn about Rhepang’s traditional medicinal herbal.Keywords: medicinal herbs, Isyo Hill’s Rhepang Muaif